Dancing towards Dictatorship: Political Songs and Popular Culture in Malawi (Nordic Journal of African Studies, 2001)
The paper describes how party politics has appropriated performances of popular art to create and entrench oppressive political culture in Malawi. Performances of popular culture were already used during the struggle for independence, and such practice was in wide use during the regime of Dr Banda, the first president of Malawi, and it has continued also after his resignation in the 1990s. The songs composed for praising the power, wisdom and excellency of the Malawi Congress Party, and particularly of its leader, Dr. Banda, were typically performed by female dancers, who used allegedly traditional modes of expression in communicating the political message. During the time of the multi-party government the practice seems to continue to be the same. The songs earlier sung in praise of Banda were later sung for Bakili Muluzi, his successor in power, and songs for mocking the previous president and his party were composed and performed during the political campaigns. However, instead of using forms of popular culture to support one party for the disadvantage of the others, there would be a need in Malawi to use such art forms for creating a 'common' political culture. (Ed.)